Analysis of the influence of the level of knowledge on respecting the inter-dialyses nursing care recommendations in patients with arterio-venous fistula treated with the method of repeated hemodialyses - Grzelewska, Aleksandra; Przybyła, Jacek; Grzanek, Marzena; Czyżewska, Katarzyna (Nursing Problems / Problemy Pielęgniarstwa, 2012)
Introduction. The necessity of implementing constant vascular access, which is the main problem of hemodialysis, begins together with progression of chronic kidney disease (CKD). Arterio-venous fistula performed from patient’s own vasculi is a vascular access standard for chronic hemodialysis (HD) purposes. Effective hemodialysis vascular access is a main condition of performing dialysis procedure and has main influence on hemodialysis patients quality of life. Patient should possess knowledge regarding proper nursing care of fistula and befully aware of the fact that the possibility of performing effective hemodialysis procedures depends on his own attitude. The nephrologic specialists are convinced that arterio-venous fistula is the line that connects the patient with the life. Aim of the study. The main aim of this study was to assess the dependence among the level of knowledge regarding compliance of the between-dialysis recommendations and employment of these recommendations by patients with fistula. Material and methods. We studied 100 patients treated at the Dialysis Ward of the Clinical Department of Nephrology, Hypertensiology and Kidney Transplantology University Clinical Hospital No. 1 in Lodz and Avitum Dialysis Department in Lodz. Studies were performed between june and october 2009. We implemented the method of diagnostic survey using questionnaire developed by authors. Questionnaire consisted of 20 questions regarding the topic of this study. Results and conclusions. The most frequent vascular access in the present study was arterio-venous fistula from the patient’s own vasculi. Informations regarding nursing care of arterio-venous fistula were sufficient for most of the hemodialysed studied patients. The source of information regarding nursing care of arterio-venous fistula for most of the hemodialysed studied patients were nurses and physicians. The most prevalent recommendations respected by patients regarding nursing care of arterio-venous fistula were hygiene and saving of the arm with fistula and checking the presence of the fistula “’noise”. The most rare recommendation respected by patients regarding nursing care of arterio-venous fistula was fistula hand not pressing during sleeping. The most prevalent compliants connected with atrio-venous fistula were pain, weakness, inefficiency, numbness and swelling of the arm with fistula.